2010
DOI: 10.1093/aje/kwq180
|View full text |Cite
|
Sign up to set email alerts
|

Case-Control Study of Body Size and Breast Cancer Risk in Nigerian Women

Abstract: Previous studies have shown that weight is inversely associated with premenopausal breast cancer and positively associated with postmenopausal disease. Height has been shown to be positively correlated with breast cancer risk, but the association was not conclusive for premenopausal women. These previous studies were conducted primarily in Western countries, where height is not limited by nutritional status during childhood. The authors assessed the association between breast cancer and anthropometric measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 34 publications
6
41
0
Order By: Relevance
“…In the largest study, involving 1,233 Nigerian breast cancer cases [25], body mass index (BMI) was inversely related to risk. However, given the typical late presentation of disease among African women, such a finding must be cautiously interpreted and may reflect weight loss due to illness.…”
Section: Role Of Previously Identified Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the largest study, involving 1,233 Nigerian breast cancer cases [25], body mass index (BMI) was inversely related to risk. However, given the typical late presentation of disease among African women, such a finding must be cautiously interpreted and may reflect weight loss due to illness.…”
Section: Role Of Previously Identified Risk Factorsmentioning
confidence: 99%
“…Hip circumference has been noted to be inversely related to risk [26]. In one of these studies, the relation with WHR persisted after adjustment for obesity [25]. Tallness has also been found to be a significant risk factor for breast cancer in two Nigerian studies [17, 25].…”
Section: Role Of Previously Identified Risk Factorsmentioning
confidence: 99%
“…The study setting and design of the Nigeria site were described in detail elsewhere (17,18). Participants from the three study sites were recruited as described below: In Nigeria, breast cancer cases were identified through the surgical oncology and radiotherapy units of the University College Hospital (UCH) in Ibadan, Nigeria which serves a population of 3 million and is the main referral center for other hospitals and thus treats the majority of the breast cancer cases in the region.…”
Section: Study Populationmentioning
confidence: 99%
“…4, 5). Since 2000, several larger studies, including prospective cohort (6)(7)(8)(9)(10)(11)(12) and case-control studies (13)(14)(15)(16) and a pooled analysis of 7 prospective cohorts (17), have examined this question in diverse populations (Table 1). For premenopausal women, both prospective cohort and case-control studies consistently report a modest (20%-40%) decreased risk of breast cancer in obese women compared with normal weight women, but similar risks for overweight and normal weight women.…”
Section: Introductionmentioning
confidence: 99%
“…For postmenopausal women, prospective cohort studies have associated increasing BMI with increasing breast cancer incidence, with some heterogeneity in the strength of this trend. Recent case-control studies in postmenopausal women, however, suggest no relationship between BMI and breast cancer risk (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%